A descriptive study on the preferred elements of selected BSID graduates in relation to cultural-responsiveness - Santos, Loren Mae B. (College of Home Economics , University of the Philippines Diliman, 2023)
Amidst globalization, the evolution of culture and the calls for cultural competence in the interior design field, it is valuable to know the current understanding of design professionals for culturally-responsive interior design in the local context. The study determined the preferred concrete and abstract elements of selected BSID graduates in relation to cultural-responsiveness, based on Asojo’s framework on design problem-solving in cultural settings (2011). The study used a descriptive approach with purposive sampling of seven (7) licensed UP BSID graduates who are currently practicing in the Philippines. The data gathering was in two phases: (1) mixed-methods online survey and (2) qualitative online interview. The data was analyzed using content and thematic analysis. It was concluded that the preferred interior elements of BSID graduates relate to cultural-responsiveness through the expression of cultural content, promotion of local sustainability, responsiveness to local social dynamics and current culture. For concrete elements, they are generally applicable with their cultural-responsiveness being based on the specifics of the design; however, there are elements that are seen as having inherent cultural content such as color, materials, and visual arts. For abstract elements, social dynamics are considered when designing interiors due to their influence on lifestyle and needs; for juxtaposition of traditional and contemporary culture, the preference is a neutral level or a level leaning towards contemporary. The findings of this study can contribute to the furtherance of studies on the Philippine built environment and the understanding of how cultural-responsiveness is approached by the local interior design industry.